Perancangan Area Restoran di Arung Rinjani berbasis Nilai Lokal dan Tanggap Covid-19 - Jasmine Chanifah Uzdah Bachtiar; Ni Ketut Ayu Intan Putri Mentari Indriani; Rini Srikus Saptaningtyas; Teti Handayani (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2023)
The North Lombok District has many fascinating and diverse tourist destination potentials. However, over the past two years, the tourism sector has experienced a decline in income due to the Covid-19 pandemic. Some tourism sectors have started to bounce back this year by designing new projects that can attract and ensure tourists form Covid-19 transmission. To develop that project, the new building attraction will be developed from local value and Covid-19 risk transmission. This research was conducted to find out how the criteria of restaurant area can be designed to support the bounce back of tourism in Arung Rinjani. This area is on the regional route of the Senaru Traditional Village. This region is predicted will be popular after the Covid-19 pandemic due to its traditional values and strategic location. Data were collected through field observations and data literature. All data will be analyzed by qualitative descriptive method to design an adaptive restaurant building criteria. The results show that the restaurant area can be designed by transforming local value and attributes to the physical form of buildings to elevate the value of locality. Meanwhile, responsive design for Covid-19 can be achieved by choosing the right furniture, changing the room layout, maintaining the adequate distance between dining areas, maximizing window openings for passive design, and educating visitors to follow health protocols during traveling. These results are expected to be design ideas and programs to design a restaurant area in Arung Rinjani.